2010
DOI: 10.2967/jnumed.110.080366
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Lipid Synthesis in Hepatocellular Carcinoma with [Methyl-11C]Choline: Correlation with In Vivo Metabolic Studies

Abstract: PET with [methyl-11 C]-choline ( 11 C-choline) can be useful for detecting well-differentiated hepatocellular carcinoma (HCC) that is not 18 F-FDG-avid. This study was designed to examine the relationship between choline metabolism and choline tracer uptake in HCC for PET with 11 C-choline. Methods: Dynamic PET scans of 11 C-choline were acquired using the woodchuck models of HCC. After imaging, [methyl-14 C]-choline was injected, and metabolites from both HCC tissue samples and the surrounding hepatic tissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 27 publications
0
21
0
Order By: Relevance
“…11 C and 18 F-F-Cho PET Increased concentrations of choline have been confirmed in surgical HCC specimens [26]. In the hepatitis viral infection-induced woodchuck model it has been shown that HCC is associated with increased transport and phosphorylation of 11 C-Cho and that the increased accumulation of radiolabelled choline reflects increased phosphatidylcholine synthesis [27,28]. A study in the same animal model has shown a small preferential uptake of 11 C-Cho compared to 18 F-fluoroethylcholine in terms of tumour-to-background contrast [29].…”
Section: C-act Petmentioning
confidence: 91%
“…11 C and 18 F-F-Cho PET Increased concentrations of choline have been confirmed in surgical HCC specimens [26]. In the hepatitis viral infection-induced woodchuck model it has been shown that HCC is associated with increased transport and phosphorylation of 11 C-Cho and that the increased accumulation of radiolabelled choline reflects increased phosphatidylcholine synthesis [27,28]. A study in the same animal model has shown a small preferential uptake of 11 C-Cho compared to 18 F-fluoroethylcholine in terms of tumour-to-background contrast [29].…”
Section: C-act Petmentioning
confidence: 91%
“…11 C-acetate instead detected 16/17 HCCs, while 11 C-choline PET detected all HCCs. Kuang et al [26], also in a woodchuck model, observed increased 11 Ccholine uptake in HCC, which was associated with choline transport and phosphorylation; the increased uptake of radiolabelled choline over time reflects increased phosphatidylcholine synthesis from cytidine 5 0 -diphosphocholine. By contrast, the surrounding hepatic tissues exhibited extensive oxidation of radiolabelled choline via the phosphatidylethanolamine methylation pathway, a major contributor to the observed physiological uptake.…”
Section: Results In Animal Modelsmentioning
confidence: 99%
“…This is actually not obvious by looking at the raw profiles and the image data. Previous preclinical studies hinted that the metabolism of radio-choline in HCC follows mainly the CDP-choline pathway that resulted in adding the saturated fatty acids in PC, while the metabolic fate of the same fluorocholine in the liver parenchymal follows PE-methylation pathway that resulted in getting the longer-chain poly-unsaturated fatty acids in PC (15). Therefore, as shown in Figure 1, not all PCs are the same!…”
Section: Applying Principle Component Analysismentioning
confidence: 99%
“…Patients would normally have their multi-phase contrast enhanced CT or MRI done before the PET scan was ordered. Regarding the advanced HCCs, anecdote results from preclinical studies showed that the imaging signal of choline uptake in these HCCs leveled down comparing to the early stage HCC, but still above liver background suggesting a possible re-partitioning the mixture between CDP-choline and PET methylation pathways in advanced HCCs for the metabolism of the choline tracers (14,15). This is worthwhile for further investigation both preclinically and clinically.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation